Hubungan Ibadah Jemaat Dan Khotbah - Marce Lodia Iba; Jonidius Illu (Universitas Katolik Widya Karya Malang, 2023)
This article was written with the aim of understanding the relationship between congregational worship and preaching properly. From this we can draw a question about what if there is no sermon in a service? can it still be said to be a worship that is in accordance with what God has commanded? So we can see that the sermon is the essence of worship. Likewise the presence of the congregation is also very important. because the benefit of the sermon is to educate, advise, admonish and teach His congregation to live according to God's Word. Preaching is one way to convey God's message. in the Christian tradition, this message is based on what is written in the Bible. Sermons can also help congregations to understand God's will in their lives. So the sermon has an important role in the growth of the congregation's faith. where what is conveyed is not only a blessing but a rebuke of sin, an introduction to Jesus Christ and the salvation that comes from Jesus Christ. So worship, congregation and preaching have a close relationship.